Diabetes Self-Management Education Patterns in a US Population-Based Cohort of Youth With Type 1 Diabetes. (January 2014) - Jaacks, Lindsay M.; Bell, Ronny A.; Dabelea, Dana; D'Agostino, Ralph B.; Dolan, Lawrence M.; Imperatore, Giuseppina; Klingensmith, Georgeanna; Lawrence, Jean M.; Saydah, Sharon; Yi-Frazier, Joyce; Mayer-Davis, Elizabeth J.; ,
Purpose: The purpose of this study is to describe (1) the receipt of diabetes self-management education (DSME) in a large, diverse cohort of US youth with type 1 diabetes (T1DM), (2) the segregation of self-reported DSME variables into domains, and (3) the demographic and clinical characteristics of youth who receive DSME. Methods: Data are from the US population-based cohort SEARCH for Diabetes in Youth. A cross-sectional analysis was employed using data from 1273 youth <20 years of age at the time of diagnosis of T1DM. Clusters of 19 self-reported DSME variables were derived using factor analysis, and their associations with demographic and clinical characteristics were evaluated using polytomous logistic regression. Results: Nearly all participants reported receiving DSME content consistent with "survival skills" (eg, target blood glucose and what to do for low or high blood glucose), yet gaps in continuing education were identified (eg, fewer than half of the participants reported receiving specific medical nutrition therapy recommendations). Five DSME clusters were explored: receipt of specific MNT recommendations, receipt of diabetes information resources, receipt of clinic visit information, receipt of specific diabetes information, and met with educator or nutritionist. Factor scores were significantly associated with demographic and clinical characteristics, including race/ethnicity, socioeconomic status, and diabetes self-management practices. Conclusions: Health care providers should work together to address reported gaps in DSME to improve patient care.